Merveilles du cirque et de la fiction dans quelques récits anglo-saxons contemporains pour adolescents et jeunes adultes - Virginie Douglas (Strenae, 2015)
This article focuses on the contemporary revival of fantasy in Anglo-Saxon young adult and children’s literature, set against the backdrop of the circus universe, such as Erin Morgenstern's The Night Circus and a few other stories. This microcosm, symbolized and saturated by the figure in the circus ring, is ideal as an escape into a secondary, magical universe, seen in recurrent references to the fairy tale, whose wonders are sometimes counterbalanced by the horrific inversion that underlies a certain fantastic anxiety. Doppelgangers abound in this fiction, which revisits the intertext of Alice's Adventures in Wonderland and Through the Looking-Glass, and offers a metafictional reflection on the artist and author figure. Indeed, because of its capacity to renew tradition, the circus constitutes an ideal setting and theme for experimenting with an innovative form of enchanted storytelling. Magic is central to these stories, which are inspired by new modes of reading and invention associated with other media besides books.